GENETICA, ECOLOGIA Y EVOLUCION DE LAS ESPECIES CHILENAS DEL GENERO RHAGOLETIS (DIPTERA: TEPHRITIDAE) - Frías, Daniel (Acta Entomológica Chilena, 2022)
This paper discuss the results of evolutionary biology of species of Rhagoletis known from Chile under the general frame of the theory of speciation. Most chilean-species are endemic, with the solé exception of R. tomatis which reaches South Perú in its distribution. These species belong to the group nova, and are different from the rest of neotropical species by the presence of an apomorphic trait in the female ovipositor. Moreover, in one of them, R. conversa, has emerged a probable atavie character, detected only in the past 10 years, which appears to constitute a paradigm of a microevolutive process in action. All the studied species with the solé exception of R . tomatis show a pupal diapause which varíes according lo some ecological factors, such as the availability of host fruits where oviposit. This diapause would also be controled by genetic factors, photoperiod, lemperature and relative humidity. The genetic studies in the chilean especies of central distribution (R. conversa y R. nova) show that changes at the level of structural genes are minimun during the evolutive process in these species, and that speciation would occur in sympatry and rather during relatively short periods if compared with the speciation process in allopatry. Nevertheless in R. tomatis the allopatric speciation is the principal factor of significative differentation in relation of the other congeneric chilean species.